FEASIBILITY OF BIOETHANOL PRODUCTION FROM ROTTEN TOMATOES (Solanum Lycopersicum) USING SACCHAROMYCES CEREVISIAE - Janet Appiah Osei (Waste Technology, 2020)
The study aimed at optimizing different fermentation conditions for bioethanol production using rotten tomatoes (Solanum lycopersicum). Rotten tomatoes were collected from sellers at Nairobi market, Kenya for six months and analysed after each time of collection in Kenyatta University Laboratory. They were physically pre-treated and enzymatic hydrolysis was performed using commercial cellulase from Aspergillus niger. Fermentation was carried out using pure culture of Saccharomyces cerevisiae (baker’s yeast). Fermentation variables were optimised at different incubation times of (24, 48, 72, 96, 120 and 144 hours) and temperatures (20oC, 25oC and 30oC). Concentration (%/v/v) of bioethanol at the end of each fermentation time was determined by the use of colorimetric method and residual sugar was determined using DNS method by Miller. Maximum bioethanol percentages of (0.17%) and (0.16%) were achieved at 24 hours and 30oC respectively. Thus, the optimum conditions for maximum bioethanol production in the study were fermentation time of 24 hours and temperature 30oC. The study results have proved the effectiveness of producing bioethanol from rotten tomatoes using baker’s yeast for fermentation.